Job search, human capital and wage inequality - Carlos Carrillo-Tudela (Institute for the Study of Labor (IZA), 2012)
The objective of this paper is to construct and quantitatively assess an equilibrium search model with on-the-job search and general human capital accumulation. In the model workers enter the labour market with different abilities and firms differ in their productivities. Wages are dispersed because of search frictions and workers' productivity differentials. The model generates a simple (log) wage variance decomposition that is used to measure the importance of firm and worker productivity differentials, frictional wage dispersion and workers' sorting dynamics. I calibrate the model using a sample of young workers for the UK. I show that wage inequality among low skilled workers is mostly due to differences in their productivities. Among medium skilled workers frictional wage dispersion and sorting dynamics are, together, as important as workers' productivity differentials. Differences in firms' productivities are also an important source of wage inequality for both skill groups and account for a large share of frictional wage dispersion. Quantitatively the model is able to reproduce the observed cross-sectional wage distribution, the average wage-experience profile and the amount of frictional wage dispersion observed in the data as measured by the Mean-min ratio.
Keywords: J63; J64; J41; J42; 330; job search; human capital accumulation; wage dispersion; turnover; Lohnstruktur; Qualifikation; Humankapital; Arbeitsuche; Arbeitsproduktivität; Arbeitsmobilität; Schätzung; Großbritannien